Menumbuhkan Karakter Sejak Dini Tentang Pembelajaran Sosial Emosional Dalam Pendidikan Dasar - Afadia Delnanda (Jurnal Pendidikan Tuntas, 2025)
Social Emotional Learning (SEL) is an approach that aims to shape students' competencies in managing emotions, establishing positive relationships, and making responsible decisions. This study aims to understand the basic concept of SEL, identify implementation challenges, explore solutions offered in the literature, and initiate the development of SEL at the elementary education level. Using a library research method with a narrative synthesis strategy, literature was collected from various trusted sources in the last five years (2019–2024). The results of the study indicate that although SEL has many benefits, its implementation is still hampered by a lack of teacher understanding, curriculum limitations, and minimal policy support. The solutions offered include teacher training, integration of SEL values in learning, and development of contextual and local culture-based programs. This study recommends the need to strengthen policies and develop an integrated SEL model in the Indonesian elementary education system.